(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: School bullying becomes a significant problem facing school –aged children world- wide and adolescents with visible cues of disability who educated in mainstream schools may be of greater risk. Aim of the study: was to assess effect of bullying on school achievement among adolescents with hearing impairment. Subjects and Methods: Research design: A case control design was conducted in that study . Setting: The study was conducted at audiometry unit and ENT outpatient clinic at zagazig university hospital and four preparatory and secondary schools at Fakous city. Subjects: a matching sample of 50 hearing impaired adolescents with hearing aids or cochlear implant and 50 control, aged 12-18 years. Tools of data collection: Three tools were used for data collection. Tool (I): A structured interview questionnaire. Tool(II) Retrospective Bullying Questionnaire (RBQ).)Tool(III): Student performance assessment form. Results: The study revealed a significant negative correlation between bullying victimization and school achievement in hearing impaired adolescents ( r= -0.445) and control group( r= -0.517)and(p=<0.001) Conclusion: Hearing impaired adolescents were more vulnerable to bullying victimization than control group. Bullying at schools is a major problem that affect school achievement negatively. Recommendations: Educational programs are required to raise awareness of children, parents and the whole community members about the phenomena of bullying, its causes, consequences and prevention .